AcrIE7 inhibits the CRISPR-Cas system by directly binding to the R-loop single-stranded DNA - Do Yeon Kim; So Yeon Lee; Hyun Ji Ha; Hyun Ho Park (Proceedings of the National Academy of Sciences, 2025)
The CRISPR-Cas system is a well-known adaptive immune system in bacteria, and a prominent mechanism for evading this immunity involves anti-CRISPR (Acr) proteins, which employ various methods to neutralize the CRISPR-Cas system. In this study, using structural and biochemical analyses, we revealed that AcrIE7 binds to the single-stranded DNA in the R-loop formed when Cascade encounters the target DNA, thereby preventing Cas3 from cleaving the DNA. This represents a different inhibition strategy distinct from previously reported Acr mechanisms and offers insights into CRISPR-Cas inhibition.